Answer:
To write √73 in exponential form, we can use the fact that the square root of a number is the same as that number to the power of 1/2. Thus, we can write √73 as 73^(1/2).
Here's how we can show this using algebraic steps:
First, we can write the square root as a fractional exponent:
√73 = 73^(1/2)
Next, we can rewrite the fractional exponent using the rule that says that a^(m/n) = (a^m)^(1/n):
√73 = (73^1)^(1/2)
Finally, we can simplify the expression by evaluating the power of 1:
√73 = (73)^(1/2) = 73^(1/2)
Therefore, √73 can be written in exponential form as 73^(1/2).